GAMBARAN JARAK DISKLUSI GIGI POSTERIOR WORKING SIDE PADA SKEMA OKLUSI CANINE GUIDANCE - Ifwandi .; Sunnati .; Isma I. Harahap (Dentistry Faculty, 2018)
anine guidance is a form of mutually protected articulation in which the vertical and horizontaloverlap of the canine teeth disengage the posterior teeth in the excursive movements of the mandible.The shorter distance to reach disclusion will have better impact to stomatognatic system. The aim ofthis study is to see the distance of posterior teeth of working side disclusion with canine guidanceocclusal scheme. This study is a descriptive survey using crosssectional study desain with 28 totalsubjects. Subject who has canine guidance occlusal scheme will be examinated the distance ofposterior teeth of working side disclusion clinically. The benchmark is made by marking the insisivuscentral maxilla by marker pen. The result of this study on right working side there are 81,8% subjecthad discluded second molar on 1mm, there are 50% subject had discluded first molar on 1 mm,54,5% subject had discluded first and second premolar on 1 mm. The result of this study on leftworking side there are 87% subject had discluded second molar on 1mm, there are 60,9% subject haddiscluded first molar on 1 mm, 56,5% subject had discluded second premolar on 1 mm, 69,6% subject had discluded first premolar on 1 mm. The conclusion of this study is distance of disclusion ofposterior teeth most often occurs on 1 mm for first and second molars, on 2 mm for second and firstpremolar.Keywords: disclusion, working side, canine guidance